A novel splice site variant in DEGS1 leads to aberrant splicing and loss of DEGS1 enzyme activity, a VUS resolved - Holly C. Beale; Victor Tse; Joanna Y. Lee; Jon Akutagawa; Yusuph Mavura; Brandon Saint-John; Allison Cheney; Dennis R. Mulligan; Guillermo Chacaltana; Martin Gutierrez; Jessica Tenney; Joseph T. Shieh; et al. (Human Genetics, 2026)
Pathogenic DEGS1 variants have been reported in individuals with autosomal recessive hypomyelinating leukodystrophy 18 (HLD18; MIM# 618404). Here we describe three participants with HLD features and a previously unreported homozygous DEGS1 5′ splice site variant, c.825+4_825 + 5delAGinsTT (NM_003676.4). We used next-generation DNA and transcriptome sequencing, cell-based splicing assays, and tandem mass spectrometry to detect and characterize the variant’s impact on DEGS1 expression. We then performed RNA structure probing and conventional antisense oligonucleotide screening to investigate molecular mechanisms for potential therapeutic intervention. We show that the splice site variant: (1) was sufficient to induce exon two skipping in most detected transcripts; (2) resulted in structural changes to the 5′ and 3′ splice site regions using RNA structure probing; and (3) corresponds to plasma sphingolipid profiles consistent with loss of sphingolipid delta(4)-desaturase activity. Our RNA and lipidomic evidence proved that the DEGS1 variant c.825+4_825 + 5delAGinsTT is pathogenic and suggested a mechanistic model that explains how exon two skipping is induced.

A novel dietary intervention with tailored behavioural support to increase legume consumption in university students: a pilot trial - Patrick S. Elliott; Lauren D. Devine; Eileen R. Gibney; Aifric M. O'Sullivan (Food Quality and Preference, 2026)

Using spatial imaginaries to understand contested senses of place and just transitions in decarbonising industrial regions - Huei-Ling Lai; Patrick Devine-Wright; Jo Hamilton (Global Environmental Change, 2026)

Realising a locally-embedded just transition: Sense of place, lived experience, and social perceptions of industrial decarbonisation in the United Kingdom - Benjamin K. Sovacool; Patrick Devine-Wright; Sarah Mander; Jordan Rowley; Stacia Ryder (Global Environmental Change, 2025)

Integrating citizens’ assemblies into local climate governance: Lessons from a UK case study - Alice Moseley; Rebecca Sandover; Patrick Devine-Wright (Environmental Science & Policy, 2025)

Do the ends justify the means? Problematizing social acceptance and instrumentally-driven community engagement in proposed energy projects - Stacia Ryder; Chad Walker; Susana Batel; Hannah Devine-Wright; Patrick Devine-Wright; Fin Sherry-Brennan (Socio-Ecological Practice Research, 2023)
Proposed energy projects across rural working landscapes play an important role in energy transitions. While community engagement has been increasingly a part of these projects, instrumental motivations for engagement and the emphasis placed on achieving social acceptance has remained uncritically examined. Here, we aim to highlight relationships between actor rationale, the structuring of engagement processes, and how communities perceive the driving forces behind engagement practices. To do so, we draw on lived experiences of communities facing proposed shale gas and wind energy projects across rural working landscapes in the UK and Canada, respectively. We find that engagement is often perceived by community members as insincere, insufficient, ineffective and instrumentally-driven. We suggest that a more community-centered approach to engagement is necessary and will require a move beyond existing engagement and acceptance practice and frameworks. This can include creating more inclusive decision-making processes where powers are balanced and designing community engagement to incorporate multiple rationales beyond achieving social acceptance of energy projects.

Induction of hemangiosarcoma in mice after chronic treatment with S1P-modulator siponimod and its lack of relevance to rat and human - Francois Pognan; J. Andreas Mahl; Maria Papoutsi; David Ledieu; Marc Raccuglia; Diethilde Theil; Sarah B. Voytek; Patrick J. Devine; Katie Kubek-Luck; Natalie Claudio; Andre Cordier; Annabelle Heier; et al. (Archives of Toxicology, 2018)

Involvement of CD45 in DNA fragmentation in apoptosis induced by mitochondrial perturbing agents - Philippe Desharnais; Geneviève Dupéré-Minier; Claudine Hamelin; Patrick Devine; Jacques Bernier (Apoptosis, 2008)